The Content and Function of Cosmopolitanism in a Selection of International Criminal Law Tribunals - Nell, Albert (South African Yearbook of International Law)
Reasoning and justifications before the international criminal tribunals and courts (ICTs) have not always strictly kept to legal rules and/or legal standards. At times, philosophical structures were used directly in argument. Consequently, this article is, in particular, concerned with cosmopolitanism in arguments and judgments from a selection of counsel and judges emanating from the Nuremberg and Tokyo International Military Tribunals as well as the ad hoc International Criminal Tribunal for the former Yugoslavia (ICTY) and the International Criminal Tribunal for Rwanda (ICTR). It aims to provide an analysis of how the different generations of ICT and the different role-players therein used cosmopolitanism in their arguments. While not a treatise on cosmopolitanism as such, the article will identify and consider several broad cosmopolitan strands relevant to the selected arguments. The ensuing analysis will propose a taxonomy of specific arguments from the selected role-players addressing (1) the existence of a homogeneous civilisation and/or common morality as a descriptive truth or falsity, (2) the progressive realisation of the international society as a normative aspiration and (3) the relationship of the duty to the international community versus that owed to the domestic community of birth. Thereafter, the article will discuss plausible functions, in addition to persuasion, served by these arguments (including winning the case, undermining or supporting the legitimacy of the ICL proceedings in their entirety and/or controlling the subsequent historical narrative). Finally, the article will situate these investigations within the broader study of philosophy at the selected ICTs.